Evaluation of patients with painful total hip arthroplasty using combined single photon emission tomography and conventional computerized tomography (SPECT/CT) – a comparison of semi-quantitative versus 3D volumetric quantitative measurements - Emilienne Barthassat; Faik Afifi; Praveen Konala; Helmut Rasch; Michael T. Hirschmann (BMC Medical Imaging, 2017)
Abstract Background It was the primary purpose of our study to evaluate the inter- and intra-observer reliability of a standardized SPECT/CT algorithm for evaluating patients with painful primary total hip arthroplasty (THA). The secondary purpose was a comparison of semi-quantitative and 3D volumetric quantification method for assessment of bone tracer uptake (BTU) in those patients. Methods A novel SPECT/CT localization scheme consisting of 14 femoral and 4 acetabular regions on standardized axial and coronal slices was introduced and evaluated in terms of inter- and intra-observer reliability in 37 consecutive patients with hip pain after THA. BTU for each anatomical region was assessed semi-quantitatively using a color-coded Likert type scale (0-10) and volumetrically quantified using a validated software. Two observers interpreted the SPECT/CT findings in all patients two times with six weeks interval between interpretations in random order. Semi-quantitative and quantitative measurements were compared in terms of reliability. In addition, the values were correlated using Pearson`s correlation. A factorial cluster analysis of BTU was performed to identify clinically relevant regions, which should be grouped and analysed together. Results The localization scheme showed high inter- and intra-observer reliabilities for all femoral and acetabular regions independent of the measurement method used (semiquantitative versus 3D volumetric quantitative measurements). A high to moderate correlation between both measurement methods was shown for the distal femur, the proximal femur and the acetabular cup. The factorial cluster analysis showed that the anatomical regions might be summarized into three distinct anatomical regions. These were the proximal femur, the distal femur and the acetabular cup region. Conclusions The SPECT/CT algorithm for assessment of patients with pain after THA is highly reliable independent from the measurement method used. Three clinically relevant anatomical regions (proximal femoral, distal femoral, acetabular) were identified.